2022
DOI: 10.3390/ijms231810731
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNAs in Systemic Sclerosis, Associations with Digital Vasculopathy and Lung Involvement

Abstract: Background and aims: Systemic sclerosis (SSc) is an autoimmune, rare multisystem chronic disease that is still not well-understood aetiologically and is challenging diagnostically. In the literature, there are ever-increasing assumptions regarding the epigenetic mechanisms involved in SSc development; one of them is circulating microRNAs. Many of them regulate TLR pathways and are significant in autoimmune balance. The aim of this study was to determine profile expression of selected microRNAs in SSc patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
0
14
0
1
Order By: Relevance
“…Patients with systemic sclerosis and FVC ≤ 70% were found to show decreased levels of miR-143 in comparison to patients having normal FVC levels. Also, miR-132 expression was shown to be higher in the dcSSc subgroup with detected active lung lesions compared to dcSSc patients with fibrotic lesions [43].…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 89%
See 1 more Smart Citation
“…Patients with systemic sclerosis and FVC ≤ 70% were found to show decreased levels of miR-143 in comparison to patients having normal FVC levels. Also, miR-132 expression was shown to be higher in the dcSSc subgroup with detected active lung lesions compared to dcSSc patients with fibrotic lesions [43].…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 89%
“…Recent studies have confirmed positive correlations between serum miRNA expression levels and the diagnosis of systemic sclerosis. Among other findings, reduced levels of miRNA-181a and miR-138, and overexpression of miR-126, miR-139-5p, miR-618, miR-132, miR-143, miR-145 and miR-155 have been detected in the serum of patients [40][41][42][43][44]. Also, a link has been shown between the pulmonary complications of SSc and the expression of individual miRNAs.…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 90%
“…Cytokeratin 17 (CK17), marginal zone protein B1 (MZB1), and leucine-rich α2-glycoprotein-1 (LRG1) appear to be potential biomarkers for SSc, with CK17 negatively associated with disease severity and higher values of CK17 protective [37,[59][60][61][62][63][64][65][66][67]. A potential therapeutic target could be endostatin, which is associated with vascular manifestations in SSc and is specifically elevated in progressive SSc; it has been considered a marker of disease severity [38,[62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
“…The chemokine CC2 (CCL2) also appears to be involved in the development of fibrosis in SSc [39][40][41][42]62]. MicroRNAs (miRNAs) are short nucleotide sequences involved in cellular regulation [37,38]. The miR-138 and miR-27a microRNAs suppress major pathways involved in epithelial-to-mesenchymal cell transition and subsequent fibrosis [37,38,45,[60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation